Performance analysis of air-to-ground heat exchanger systems: a detailed investigation of finned and un-finned tube designs for oil pipeline cooling - Hummood, Eman A.; Hasan, Mushtaq I.; Rashid, Farhan Lafta; Al-Obaidi, Mudhar A.; Ameen, Arman (Frontiers in Energy Efficiency, 2025)
Using a comprehensive analysis, this research intends to assess the performance of an air-to-ground heat exchanger system designed for cooling air compression equipment in oil pipeline operations. Both numerical simulations and experimental investigations are conducted to compare the performance of un-finned tubes with finned tubes of different configurations, including square perforated annular fin tubes, annular fin tubes and circular perforated annular fin tubes. In turn, this would identify optimal configurations for maximum heat transfer. The system uses a 1.5 m long PVC pipe with a 6-inch diameter, buried 3.5 m underground. A relatively stable ground temperature of approximately 30°C at a depth of 3 m throughout the year contributes to the cooling efficiency of the system during summer and heating in winter. The results obtained between July and August 2023 indicate that annular finned tubes can provide superior heat transfer rates in both experiments and simulations compared to un-finned tubes. Furthermore, annular fin tubes demonstrate the highest cooling efficiency. However, they also exhibit the greatest pressure drop among the tested configurations. Overall, this study highlights the effectiveness of the proposed system in delivering cooling under demanding environmental conditions.